On $I$ and $I^K$-Cauchy nets and completeness - Pal, Sudip Kumar (Sarajevo Journal of Mathematics, 2024)
In this paper we study the concept of $I^K$-Cauchy nets which is more general form of $I^*$-Cauchy nets. We also investigate its relation with the concept of $I$-Cauchy nets and study the completeness of a uniform space in terms of $I^K$-Cauchy nets. Subsequently our results extend similar results of Das and Ghosal. 2010 Mathematics Subject Classification. Primary: 54A20; Secondary: 40A35, 54E15